2022
DOI: 10.1126/sciadv.abm6247
|View full text |Cite
|
Sign up to set email alerts
|

Multiple approaches converge on three biological subtypes of meningioma and extract new insights from published studies

Abstract: One-fifth of meningiomas classified as benign by World Health Organization (WHO) histopathological grading will behave malignantly. To better diagnose these tumors, several groups turned to DNA methylation, whereas we combined RNA-sequencing (RNA-seq) and cytogenetics. Both approaches were more accurate than histopathology in identifying aggressive tumors, but whether they revealed similar tumor types was unclear. We therefore performed unbiased DNA methylation, RNA-seq, and cytogenetic profiling on 110 primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 54 publications
7
66
0
Order By: Relevance
“…A 2022 study classified meningiomas into three methylation groups, similar to the study by Sahm and co-workers ( 102 ), and showed that DNA methylation is more accurate than histopathology in identifying high-risk tumors and is closely correlated with gene expression in meningiomas ( 118 ). This study further compared the predictive accuracy of DNA methylation with that of RNA-sequencing and cytogenetics and found a strong concordance between these groups.…”
Section: Dna Methylation Patternsmentioning
confidence: 80%
See 1 more Smart Citation
“…A 2022 study classified meningiomas into three methylation groups, similar to the study by Sahm and co-workers ( 102 ), and showed that DNA methylation is more accurate than histopathology in identifying high-risk tumors and is closely correlated with gene expression in meningiomas ( 118 ). This study further compared the predictive accuracy of DNA methylation with that of RNA-sequencing and cytogenetics and found a strong concordance between these groups.…”
Section: Dna Methylation Patternsmentioning
confidence: 80%
“…This study further compared the predictive accuracy of DNA methylation with that of RNA-sequencing and cytogenetics and found a strong concordance between these groups. The authors also demonstrated that both DNA promoter methylation and copy-number variability correlated with differential gene expression ( 118 ). Further, a recent study analyzed four types of alterations together, namely DNA somatic copy-number aberrations, DNA somatic point mutations, DNA methylation, and messenger RNA abundance, and found that these could be classified into four groups (M1–4) owing to distinct biology as follows: immunogenic (M1), benign NF2 wild-type (M2), hypermetabolic (M3), and proliferative (M4) ( 12 ) ( Table 2 ) .…”
Section: Dna Methylation Patternsmentioning
confidence: 99%
“…In these aggressive phenotypes, genetic analyses have already confirmed the presence of gross chromosomal and also specific gene imbalances (gains, rearrangements and intra-or inter-translocations, frame-shift deletions/insertions, in-frame fusions or point-driver mutations) (18)(19)(20). Numerical imbalances in chromosomes including chromosome 22, fragment deletions on chromosome 1p and 2q33-q35, specific regional chromosome 6p21-p22, 13q33, 17 and 19 amplifications have been also detected and reported (21)(22)(23)(24)(25). Furthermore, a variety of single nucleotide polymorphisms have been also recognized (26).…”
Section: Discussionmentioning
confidence: 99%
“…Integrated use of DNA methylation, RNA sequencing, and cytogenetic profiling by Patel et al on 110 grade 1 and II meningiomas according to the 2016 WHO classification system revealed two benign and one malignant tumor group closely resembling the previously established type A, B, and C classifications (103). Methylation analysis further distinguished these groups as tumors with balanced methylation (Meth 1), hypomethylation (Meth 2), and hypermethylation (Meth 3) (103).…”
Section: Molecular Profiling For Meningioma Stratificationmentioning
confidence: 91%